(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
This contribution aims to deepen a piece of Guido Ceronetti’s poetic production, taking into consideration, starting from a specific section, the evolution that, from the first traces found in the two debut collections – Nuovi salmi. Psalterium primum (Pacini Mariotti, 1955) and Nuovi salmi (Stamperia Impronta, 1957) – and from the collection Poesie, Frammenti, Poesie separate (Einaudi, 1968), leads to the opera omnia, La distanza. Poesie 1946-1996 (Rizzoli, 1996), and to the anthology Sono fragile sparo poesia (Einaudi, 2012). This paper focuses its attention on the changes made to the inner architecture and on the reorganization of the indexes of the third section, from the original nucleus of Poesie separate to Suggerimenti dell’emozione. Dealing elsewhere with the analysis of textual variants, this article can be placed on a line close to the so-called philology of structures: it describes the poetic organism in its evolution, in the different phases in which it has been crystallized, revised and expanded by the author.